Using manual versus mechanized glide path instruments and ProTaper Gold versus ProTaper Next systems in curved canals: micro-CT study - Breno Nappi VENTURA; Giulio GAVINI; Elaine Faga IGLECIAS; Laila Gonzales FREIRE; Celso Luiz CALDEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to evaluate the root canal shaping effect of ProTaper Gold (PTG) versus ProTaper Next (PTN) instrumentation systems, and of a manual #15 K-type file (K15) versus the ProGlider (PG) mechanized instrument for glide path creation, in severely curved mesial canals. Twenty-four mandibular molars with two separate mesial canals were anatomically matched using computed tomographic scanning, and then divided into two groups (n=12) according to the glide path instrument used, either K15 or PG. In all teeth, the PTG system was used to prepare the mesiobuccal canal, and the PTN, the mesiolingual canal. The teeth were scanned by computed microtomography, before and after root canal preparation, and the values of the initial volume, final volume, volumetric variation, untouched walls, and canal transportation variables were determined. The data were analyzed using the two-way ANOVA test, and the Tukey test for multiple comparisons. There was no significant difference among the study groups regarding volumetric variation or root canal transportation, either in the cervical, middle or apical thirds, or in the entire root canal (p>0.05). In the apical third, the percentage of untouched walls was significantly higher in groups using K15 than in those using PG (p<0.05), namely 33.144% and 23.285%, respectively, irrespective of the instrumentation system. In the other regions, there was no difference between K15 and PG regarding this variable. It was concluded that PG was associated with a lower rate of untouched walls in the apical region than K15.